MANY NEW AIRLINES ESTABLISHED IN INDONESIA AFTER AVIATION LAW LAUNCH 2009?, SAFETY LEFT BEHIND? - arista atmadjati (LIAISON JOURNAL OF BEST, 2022)
Public transportation safety assurance is an absolute requirement in the implementation of public sector transportation . There is no tolerance for safety guarantees, so Therefore the regulator (government) must ensure safety has a single standard so that it does not created spaces for negotiation or even bargaining related to safety. Still remember in our memory the air transportation accident in October 2018. Then, Lion Air's Boeing 737 Max 8 with registration number PK-LQP crashed in Tanjung Pakis, north Karawang, West Java, which the victim in the death of 189 passengers. The plane plunged into the waters of Karawang after a 13-minute flight from Jakarta. Then on the March 2019 a similar plane belonging to Ethiopian Airlines crashed just 6 minutes after takeoff from Addis Ababa which resulted in the death of 157 passengers. Those two incidents should be an important lesson for transportation stake holder so as never to underestimate safety. Again, in context In public transportation, passenger safety must always be number one. Maybe even must be considered as a sacred thing so that no one dares to ignore it. The principle of safety must always come first is actually not a monopoly on air transportation, land and sea transportation should apply the same principle. Safety passengers is an absolute guarantee that must be given.Keywords :There is no excuse for every single error in the space or we will fatal in safety.